Quranic Hermeneutics and Sufism of Syaykh Abd al-Qadir al-Jilani - Irwan Masduqi (Center for Research and Development of Religious Literature and Heritage, 2015)
Syaykh Abdul Qadir al-Jilani is the founder of Tariqah Qadiriyyah. His teaching is highly respected by the leaders of many Islamic traditional boarding schools in Indonesia. They have accepted his teachings from his works entitled Futµh al-Gayb, al-Fat¥ al-Rabban³, al-Gunya li °alib³ °ar³q al-¦aqq, and Kit±b Sirr al-Asr±r wa Ma©h±r al-Anw±r. Then, in 2009, there was a discovery of al-Jilani's commentary of Qur’an entitled al-Faw±ti¥ al-Il±hiyyah wa al-Maf±ti¥ al-Gaybiyyah al-Muw±«³hah li al-Kal³m al-Qur’±niyyah wa al-Hik±m al-Furq±niyyah. As one of teachers traditional Islamic boarding school, I am interested in examining the authenticity of al-Faw±ti¥ al-Il±hiyyah wa al-Maf±ti¥ al-Gaybiyyah al-Muw±«³hah li al-Kal³m al-Qur’±niyyah wa al-Hik±m al-Furq±niyyah. This research also discusses the interpretation of the Al-Qur’an in the view of Shaykh Abd al-Qadir al-Jilani and his methods.